A Comparative Study of Kinetic Reaction Schemes for the Isomerization Process of the C6 Series - Diana K. Díaz-Cervantes; Arturo Elías-Domínguez; Ángel Castro-Agüero; Fernando Pérez-Villaseñor; Arturo Ortíz-Arroyo; Friné López-Medina; Eduardo López-López; Edith Osorio-de-la-Rosa (Applied Sciences)
The conversion of n-hexane into its isomers is highly relevant in the petroleum refining industry due to its contribution to improving gasoline quality by increasing the octane number. This study presents a comparative analysis of eight reaction schemes for the C6 series isomerization process. It was demonstrated that incorporating rigorous chemical equilibrium information, based on experimental data, yields virtually identical results across all schemes, enabling a detailed analysis. Five schemes were taken from the literature, two were modified to ensure linear independence, and one was proposed in this study under the same criteria. It was confirmed that using linearly independent schemes reduces the number of reactions without affecting model accuracy, facilitating its numerical solution. Each scheme was evaluated using simulations under industrial conditions with a kinetic model that includes 16 reactions. The results show predictions with average errors of 1.44% in reactor outlet temperature and 3.25% in molar flow rates. The kinetic constants for each reaction of the C6 series were generalized, ensuring their invariability regardless of the scheme used, allowing for their application to different schemes and eliminating the need for individualized tuning of the isomerization reactors in the process under study.